A nanoconfined loading strategy for highly efficient siRNA delivery and cancer therapy. (April 2022) - Zhang, Wangcheng; Zhang, Yuxi; Luo, Yingli; Chen, Senbiao; Huang, Qiaoyi; Cao, Zhiting; Liang, Ming; Yang, Xianzhu
Highlights: The nanoconfined loading strategy significantly enhanced the electrostatic interaction of cationic material and siRNA. This nanoconfined strategy reduced by 70% amount of cationic material usage compared to conventional absorption strategy. The prepared NCAPAMAM/siRNA improved tumor cell uptake of siRNA by releasing PAMAM/siRNA at acidic tumor microenvironment. NCAPAMAM/siRNA carrying siPD-L1 efficiently suppressed PD-L1 expression for cancer immunotherapy. Graphical Abstract: ga1 Abstract: Cationic polymers and lipid-based nanocarriers remain the main systems of nucleic acid drug delivery; however, their high cytotoxicity and low loading efficiency limit their clinical application. Herein, we report a nanoconfined loading strategy for highly efficient loading and delivery of small interfering RNA (siRNA). Through this design strategy, the electrostatic interactions between siRNA and the cationic moieties of poly(amidoamine) (PAMAM) in the nanocarrier material were confined to nanoscale spaces, which significantly increased the siRNA loading capacity (complete loading was achieved at an amino groups/phosphate group (N/P) ratio of 3) compared to the conventional electrostatic absorption strategy (with a complete loading at N/P of 10). Moreover, the PAMAM/siRNA was released in tumor tissue through the tumor-acidity-sensitive linkage, resulting in enhanced cellular uptake of siRNA. Notably, by carrying siRNA targeting polo-like kinase 1 (Plk1), the prepared nanocarrier high efficiently downregulated target genes in vitro and in vivo and efficiently inhibited tumor growth in breast tumor. In addition, the nanocarrier carrying siRNA targeting programmed death-ligand 1 (PD-L1) exhibited efficient inhibition of CT26 colorectal tumor through activation of the antitumor immune response. The nanoconfinement strategy proposed in this study provides a new avenue to explore cationic material-mediated systems of nucleic acid drug delivery.